AN ANALYSIS OF COPING STRATEGY FOR NURSE CARE IN FACING PSYCHIATRIC PATIENTS IN INTENSIVE SERVICE UNITS (UPI) AT PSYCHIATRIC HOSPITAL OF DR. SOEROJO MAGELANG - Noviana, Isti; Andamari, Sri Respati (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2020)
This study aims to get understanding on how the anxiety coping strategies of psychiatric nurses in handling patients who still feel anxious in the Intensive Service Unit (UPI). The method used in this study is a qualitative research by taking data based on the condition of natural objects. The study is conducted on psychiatric nurses in the Intensive Service Unit at Prof. Dr. Soerojo psychiatric Hospital in Magelang. The respondents of this study are taken from stratified purposive sampling that the writers take 2 female psychiatric nurses from female UPI and 3 male psychiatric nurses from Male UPI. Data are collected by observation and interview. The results show that the coping strategies that emerged from each subject differr one another, not all aspects of the coping strategy were used by the respondents. This means that by varying the coping strategies emerging from each respondent can be used as a reference as a study learned by individuals with the same conditions experienced by the respondents.